A Review of Fabrication Method of Casting Metal Matrix Composite Materials in Liquid State - Kamandanu, Ikhsan; Pranoto, Hadi (Institute for Research on Innovation and Industrial System (IRIS), 2025)
This article reviews the fabrication methods of metal matrix composites (MMCs) in liquid state. Metal matrix composites, especially aluminium metal matrix composites (AMMCs), are widely used in automotive, aviation, and medical industries due to their superior properties such as low density, good wear resistance, and specific strength. Liquid-based manufacturing processes include infiltration, stir casting, centrifugal casting, squeeze casting, vacuum die-casting, compocasting, and rheocasting. Each method offers specific advantages in reinforcement distribution, cost efficiency, and complex shape manufacturability. Infiltration is effective in achieving good interfacial bonding; stir casting is popular because it is simple and economical for mass production; centrifugal casting excels in forming high-density and wear-resistant composites; squeeze casting and vacuum die casting increase the strength and density of composites; while compocasting and rheocasting offer more homogeneous microstructure and grain refinement. This review shows that the selection of method should be based on the specific application requirements and material characteristics to achieve optimum mechanical properties. With improvements in technology and control of process parameters, liquid casting methods offer significant potential for the manufacture of high-performance structural and functional components.